KARAKTERISTIK DINAMIS PEGAS UDARA Dynamics Characteristic of Air Suspension - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Research on the dynamics characteristic of an air suspension had been conducted in the Laboratory of Acoustic and Vibration Mechanical Engineering Department, Faculty of Engineering Gadjah Mada University. The equipment was selfmade and was not a representation of any kind of air spring brand. The results were expressed as "Mass Pressure Ratio", that was, the ratio of mass and the air pressure inside the air suspension. The air pressures were varied from 90 cm H2O to 15 cm H2O with 5 cmH2O pressure step. For both transient and steady state conditions, the lateral and transversal modes were examined. The results show that the spring coefficient in lateral and transversal modes decrease as its MPR increase. The damping ratio in lateral mode increase parabolically as its MPR increase. Good performance will be achieved by an air spring which is used as vibration isolator in lateral mode as long as the working frequency is more than 25 Hz. The use of air suspension as vibration isolator in transversal mode is not recommended. Additional equipment should be introduced to improve its damping ratio when an air suspension is used as shock absorber both in lateral and transversal modes.